Ethnic entrepreneurs in Malaysia: motivations and challenges - Mohd Wahid, Siti Daleela; Ismail, Shafinar; Mhd. Sarif, Suhaimi (International Academic Institute for Science and Technology, 2019)
There is a growing number from 1,002,000 to 1,169,000 (2010 to 2014) of ethnic entrepreneur?s involvement in Malaysia especially in small business activities. It is also estimated in 2015 that 6.7 million ethnic entrepreneurs concentrating in all walks of economics activities in the country. Some of them coming as an under-skilled migration, however, ending up with started up their own businesses as jobs opportunities were found to be hard for them. Moreover, certain businesses are changing hands from the local owners to ethnic owners. While this issue has been discussed, unfortunately, only few the study attempts to understand the motivation and challenges of ethnic entrepreneurs that help to promote the economic growth. Therefore, the objectives of this study are twofold: (1) To explore the motivational factors faced by ethnic entrepreneurs (2) To understand the challenges they might face in Malaysia. To serve its objectives, a qualitative method is needed to be employed. A semi-structured interview will be conducted among the ethnic entrepreneurs (owners/managers of businesses) to document their views towards the ethnic entrepreneur?s motivation and challenges. The practical implication is contributed to the literature review of ethnic entrepreneurship and reviewing the Industrial Relations Act 1967 and Employment Act 1955 to ensure the law is in line with needs of local and foreign employees-employers, as well as the needs of an industrializing nation's workforce.